2019
DOI: 10.4103/ijpvm.ijpvm_508_18
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the most effective hydatid cyst fluid fraction for anticancer vaccination of 4T1 breast tumor-bearing mice

Abstract: Background: The hydatid cyst fluid antigens have high homology with cancer cell antigens and also exhibit considerable immunogenicity. Therefore, their utilization for cancer immunization can cause an effective antitumor immune response. However, the main challenge is identifying the most effective antigens for this purpose. Methods: Hydatid cyst fluid fractions including the glycolipid fraction, glycoprotein fraction, 78 kDa fraction, and antigen B fraction were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Similarly, another study examining the effects of HCF on hepatocellular carcinoma in mice reported a significant suppression of tumor growth and angiogenesis. These findings suggest that HCFand its antigens may have potential therapeutic applications in cancer treatment [27]. Animal models provide a valuable tool for further investigation and can help to identify potential mechanisms of action and optimal treatment strategies.…”
Section: Animal Models: Effects On Tumor Growthmentioning
confidence: 94%
“…Similarly, another study examining the effects of HCF on hepatocellular carcinoma in mice reported a significant suppression of tumor growth and angiogenesis. These findings suggest that HCFand its antigens may have potential therapeutic applications in cancer treatment [27]. Animal models provide a valuable tool for further investigation and can help to identify potential mechanisms of action and optimal treatment strategies.…”
Section: Animal Models: Effects On Tumor Growthmentioning
confidence: 94%